O movimento promocional no telejornalismo: estratégias discursivas da RBS TV no Jornal do Almoço - Tarouco, Cristiano (2012)
Although News broadcasting focuses on information, promotion also permeates its construction in several levels, as a result of commercial logics that guide tv newscast planning towards the creation of effects of meaning. Thereof, this research approach discursive strategies employed when stressing narratives that are distinguished by the articulation between information and promotion. Thus, the investigation aims to analyze self-promotional discursive strategies used by RBS TV during local coverage by affiliates in the countryside of the state. For this reason, the theoretical framework approach of this study considers the context of brazilian televisual communication, the procedures for televisual promotion, and Newscast discursive strategies. The corpus was obtained from RBS TV RS affiliated broadcasters, which were analyzed during 18 months between 2010- 2011, and selected for further analysis according to the local production of special anniversary editions of the Jornal do Almoço newscast, with priority for those that devoted complete blocks to the celebration. In this study, which aims to investigate the televisual media production, the discursive semiotic conception was upgraded and expanded in order to handle the challenge of studying deliberation and goals of the subject that speaks, concerning how a tv newscast narrative articulates information along with promotion. The corpus is validated by the peculiarities observed in affiliated broadcasters, which must operate in a short period of time reserved for local productions, subjected to head-end production and standardized formats. The evaluation of local Jornal do Almoço special anniversary editions showed that, in these occasions, the teams have more development liberties for the newscast enunciation, in order to better approach the local audience. The reason for that relies on RBS TV interest in maintaining their audience leadership, using self-reference as discursive strategy.